INDONESIA’S LEGAL PROTECTION AGAINST BLOCKCHAIN TECHNOLOGY DEVELOPMENT RISKS: ANALYSING THE GLOBAL PERSPECTIVE ON CRYPTOCURRENCY REGULATION - Ariella, Audrey Davita; Yusuf, Danisha Vanya; Dwi Atmaja, Bima Kumara (Fakultas Hukum Universitas Udayana, 2026)
The current article examines Indonesia’s legal protection through current national regulations and its sufficiency against inherent risks of blockchain technology development, especially crytocurrency, by comparing them to other regulatory approaches around the globe. The lightning-speed of cryptocurrency’s growth as a digital asset has created both economic opportunities yet legal issues, including the commonality of fraud, scams, and “rug pulls” due to inadequate consumer protection. As such, it is of no surprise that effective regulations are becoming a more combmon need. The research method applied is one of the normative legal research, implementing statute and case approaches. Primary legal materials include statutory regulations governing cryptocurrency in Indonesia, while secondary materials consist of academic literature, journal articles, and comparative regulatory studies from other jurisdictions. While Indonesia only recognized cryptocurrency as a digital, tradable asset rather than a legal tender, this function may still bring forth issues in the future as cryptocurrency is inherently decentralized. A contrario, regulatory frameworks implemented in jurisdictions such as the European Union, the United States, and Japan do recognize cryptocurrency as a legal tender and thus should face more issues. Yet, with effective strengthening of their legal framework, it may serve Indonesia to heed and take reference of those systems. In particular, Japan’s licensing-based supervisory model could perhaps offer a relevant approach for improving legal protection and enhancing regulatory oversight in Indonesia’s cryptocurrency ecosystem.